EXPLORATION OF MONUMENTAL TEXTILE TECHNIQUES AS A SENSORY INTERVENTION MEDIUM FOR CHILDREN WITH SPECIAL NEEDS THROUGH A DESIGN THINKING APPROACH - Vera Utami Gede Putri; Melly Prabawati; Neddyana Pahlawaty; Kholifatul Novita Ningsih; Prince Clinton Immanuel Christian Damanik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the use of monumental textile techniques as a multisensory intervention medium for children with sensory processing disorders through a Design Thinking approach. Children with sensory challenges often display repetitive behaviors as self-regulation strategies due to difficulties in processing tactile and proprioceptive stimuli. Using qualitative methods including participatory observation, interviews, studio experiments, and limited trials involving three children aged 3 to 7 years, this research developed textile-based sensory media employing ruffling and tucking techniques The findings show that varied textures effectively stimulate sensory responses, increase attention span, and promote positive emotional engagement. The intervention also redirects repetitive behaviors into more structured and adaptive exploratory activities. The Design Thinking approach ensures that the developed media are user-centered, functional, and contextually relevant. However, effectiveness depends on individual sensory profiles, requiring personalized implementation and professional supervision. Overall, monumental textile media demonstrate strong potential as innovative sensory intervention tools to support emotional regulation and adaptive behavior in children with special needs.